Evaluation of skin prick test sensitivity for 37 allergen extracts in atopic patients with nasal polyposis - Z A Ashour; Hosam Rabee; H A El-Melegi; Mohamed Yousef Attia; Hesham Sanad (SpringerOpen, 2014)
Background Skin prick test (SPT) is a gold standard test for diagnosis of allergic [immunoglobulin E (IgE)] diseases. There is a subset of patients who have positive nasal provocation to allergens, despite having a negative SPT. The aim of our study was to evaluate SPT sensitivity in atopic patients with allergic nasal polyposis. We chose 56 patients (discussion with the patients regarding the benefits and hazards of the study was performed and informed consent was taken from them) with bilateral nasal polyposis (as diagnosed by full history taking, clinical examination, nasal endoscopic examination, and sinonasal computed tomography) who proved to be allergic (by full history taking, clinical examination, positive serum total IgE, serum-specific IgE, and tissue-specific IgE). SPT was performed using a panel of 37 allergen extracts. Results A total of 15 patients showed negative Results to SPT representing 26.8%. In all, 41 patients showed positive Results to SPT (73.2%); six patients (14.6%) showed positive result to only one allergen (monosensitized), whereas the remaining patients were polysensitized. The most common allergens found to be positive by SPT were: 'House Dust' with positive Results in 19 patients representing 46.3% of patients with positive Results to SPT (41 patients), followed by 'Pollens' with positive Results in 18 patients (43.9%), 'House Dust Mite' with positive Results in 17 patients (41.5%), and then 'Molds' with positive Results in 14 patients (34.2%). Conclusion Negative SPT does not exclude allergy in atopic patients with nasal polyposis. Thus, before delivering a diagnosis of nonallergic rhinitis in patients with negative SPT to common allergen, further tests are needed. We recommend further studies to evaluate the prevalence, immunopathology, and management of local allergic rhinitis.